2021
DOI: 10.1371/journal.pgen.1009832
|View full text |Cite
|
Sign up to set email alerts
|

AKAP13 couples GPCR signaling to mTORC1 inhibition

Abstract: The mammalian target of rapamycin complex 1 (mTORC1) senses multiple stimuli to regulate anabolic and catabolic processes. mTORC1 is typically hyperactivated in multiple human diseases such as cancer and type 2 diabetes. Extensive research has focused on signaling pathways that can activate mTORC1 such as growth factors and amino acids. However, less is known about signaling cues that can directly inhibit mTORC1 activity. Here, we identify A-kinase anchoring protein 13 (AKAP13) as an mTORC1 binding protein, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…A recent study showed that AKAP13 inhibits mammalian target of rapamycin complex 1 (mTORC1), which was present in our enrichment analysis as “mTOR signaling pathway” ( Table 3 ). Furthermore, the degree of AKAP13 expression in lung adenocarcinoma cell lines correlates with mTORC1 activity [ 35 ]. Metformin’s anti-inflammatory effect has been shown to occur through eventual AMPK activation, which also inhibits the mTOR signaling pathway [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that AKAP13 inhibits mammalian target of rapamycin complex 1 (mTORC1), which was present in our enrichment analysis as “mTOR signaling pathway” ( Table 3 ). Furthermore, the degree of AKAP13 expression in lung adenocarcinoma cell lines correlates with mTORC1 activity [ 35 ]. Metformin’s anti-inflammatory effect has been shown to occur through eventual AMPK activation, which also inhibits the mTOR signaling pathway [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that AKAP13 inhibits mammalian target of rapamycin complex 1 (mTORC1), which was present in our enrichment analysis as "mTOR signaling pathway" (Table 3). Furthermore, the degree of AKAP13 expression in lung adenocarcinoma cell lines correlates with mTORC1 activity 36 . Metformin's anti-inflammatory effect has been shown to occur though eventual AMPK activation, which also inhibits the mTOR signaling pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…AKAP13 scaffolds PKA next to mTORC1, leading to Raptor Ser791 phosphorylation and mTORC1 inhibition. Additionally, AKAP13 plays a role in the mTORC1-mediated processes of cell proliferation, cell size, and lung tumorigenesis ( Zhang et al, 2021 ). Previous studies found that AKAP13 promotes ERK signaling ( Smith et al, 2010 ) and displays GEF activity for RhoA, promoting activation of p38 α ( Pérez López et al, 2013 ).…”
Section: Upstream Stimuli That Regulate Mtorc1 Activitymentioning
confidence: 99%
“…ERK signaling is known to activate mTORC1 by inhibiting TSC ( Ma et al, 2005 ), and p38 α has been previously reported to negatively alter TSC function by promoting TSC and 14-3-3 binding ( Li et al, 2003 ; Shumway et al, 2003 ). However, the pharmacological inhibition of ERK signaling did not change Raptor Ser 791 phosphorylation, and p38 α depletion did not alter mTORC1 activity ( Zhang et al, 2021 ). Similarly, it was found that TSC knockout cells also did not affect Raptor Ser791 phosphorylation ( Jewell et al, 2019 ), indicating that AKAP13-mediated regulation of mTORC1 may be independent of ERK and p38 α signaling.…”
Section: Upstream Stimuli That Regulate Mtorc1 Activitymentioning
confidence: 99%